Komunikacja niewerbalna osób uzależnionych od alkoholu. Przegląd badań - Doroszuk, Marta; Zagórska, Wanda (Kwartalnik Naukowy Fides et Ratio, 2017)
The article is a review of the world’s current research on non-verbal communication of alcohol addicts. Many studies show that these individuals are less capable of recognition of the emotional facial expression of the other person and, consequently, their communication is less effective than the non-dependent. In addition, the problem is for them both to understand the intention of the other person and to properly communicate their needs and emotions. Alcohol addicts have more problems maintaining positive relationships with others, often due to deficits in nonverbal communication.